Where the wild things are - Sendak, Maurice (Harper Collins, 1963)
The story focuses on a young boy named Max who, after dressing in his wolf suit, wreaks such havoc through his household that he is sent to bed without his supper. Max's bedroom undergoes a mysterious transformation into a jungle environment, and he winds up sailing to an island inhabited by monsters, simply called the Wild Things. The Wild Things try to scare Max, but to no avail. After stopping and intimidating the creatures, Max is hailed as the king of the Wild Things and enjoys a playful romp with his subjects.